Confined-unconfined flow in a horizontal confined aquifer - Li, Ling; Lockington, D A; Barry, D A; Parlange, J Y; Perrochet, Pierre (My University, 2003)
Mixed confined and unconfined groundwater flow occurs in a bounded initially dry aquifer when the hydraulic head at the side boundary suddenly rises above the elevation of the aquifer's top boundary. The flow problem as modelled by the Boussinesq equation is non-trivial because of the involvement of two moving boundaries. The transformed equation (based on a similarity transformation) can, however, be dealt with more easily. Here, we present an approximate analytical solution for this flow problem. The approximate solution is compared with an 'exact' numerical solution and found to be a very accurate description for describing the mixed confined and unconfined flow in the confined aquifer. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: mixed flow; Boussinesq equation; moving boundary; sorptivity; Boltzmann; transformation; BOUSSINESQ EQUATION; GROUNDWATER